Small Business Employees’ Intention to Learn: Establishing Research Directions (Journal of Organizational Psychology, 2017)
The following paper overviews the importance of learning in small business and entrepreneurship. It examines the notions of behavioral intentions and behavior in particular with respect to small business and entrepreneurship and intention to learn. The paper also examines the roles that learning affordances, engagement, and self-directed-learning style play in the links between employee intentions to learn and their learning behavior. In total 15 propositions for future research are identified and described and a research agenda is briefly discussed.
Keywords: Organizational Psychology; Business; entrepreneurship